High temperature molecular motions within a model protomembrane architecture. Issue 24 (14th June 2022) - Misuraca, Loreto; Matsuo, Tatsuhito; Cisse, Aline; LoRicco, Josephine; Caliò, Antonio; Zanotti, Jean-Marc; Demé, Bruno; Oger, Philippe; Peters, Judith
Abstract : Different molecular motions within protomembranes probed by quasi-elastic neutron scattering. Abstract : Modern phospholipid membranes are known to be in a functional, physiological state, corresponding to the liquid crystalline phase, only under very precise external conditions. The phase is characterised by specific lipid motions, which seem mandatory to permit sufficient flexibility and stability for the membrane. It can be assumed that similar principles hold for proto-membranes at the origin of life although they were likely composed of simpler, single chain fatty acids and alcohols. In the present study we investigated molecular motions of four types of model membranes to shed light on the variations of dynamics and structure from low to high temperature as protocells might have existed close to hot vents. We find a clear hierarchy among the flexibilities of the samples, where some structural parameters seem to depend on the lipid type used while others do not.